The connection between the vector minimising problem and convex programming problem - Jasilionis, R.; Rybakovaitė, P. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Ю. Ясилионис, П. Е. Рыбаковайте. Связь векторных задач минимизации с задачами выпуклого программирования R. Jasilionis, P. Rybakovaitė. Vektorinės minimizacijos uždavinių ryšys su iškilo programavimo uždaviniais